Paving the way for Methane Hydrate formation in the confined nanospace of metal-organic frameworks - Dr Enrique Ramos-Fernández; Dr Svemir Rudic; Ms Mirian Casco; Professor Joaquin Silvestre-Albero (ISIS Facility, 2015)
The main goal of the present proposal is to evaluate the methane hydrate formation in nanocavities of ZIF-90 using inelastic neutron scattering (INS) measurements. Recently, we have measured in TOSCA the formation of methane hydrate on ZIF-8. We have found that the methane hydrate is formed at the external surface. The exclusion of the hydrate formation process from the inner cavities of ZIF-8 is due to the highly hydrophobic nature of ZIF-8 that avoids the water to access the porosity. Potentially, the methane storage capacity would be further improved if the internal volume of the ZIF is also used for hydrate formation. It is well known from literature that ZIF-90 can be filled with water at high relative pressure (>0.4), indicating weak MOF-water interactions. From our previous knowledge, this MOF might be postulated as a promising material to growth methane hydrate inside.